Assessment of Technical and Financial Risk Through Feasibility Studies - Aspinall T. O (The Australasian Institute of Mining and Metallurgy, 1994)
This paper discusses the identification and assessment of risk for mining developments particularly for open pit mining. A distinction between sensitivity studies and risk analysis is developed, demonstrating the importance of geological and mining engineering judgement -as applied by experienced practitioners to the analysis and assessment of risk in such projects. Technical and financial risk analysis are discussed under: ò mineral resources and ore reserves; ò mining and processing methods; ò project construction; ò financing; and ò costs and commodity pricing predictions.